Integrating ultrasonic neuromodulation with fiber photometry - Vasan, Aditya; Magaram, Uri; Patel, Janki; Friend, James; Chalasani, Sreekanth H. (Frontiers in Acoustics, 2023)
Ultrasound has been used to modulate neural activity in rodents and primates; however, combining ultrasound stimulation with in vivo imaging in freely moving animals has been challenging. Here, we design and validate a transducer to overcome these challenges in the rodent. We develop a head-mounted ultrasound transducer that can be combined with a fiber photometry system. This combination allows us to monitor ultrasound-evoked responses in striatal neurons in awake and freely moving animals. Together, this system allows for a high-resolution analysis of ultrasound-evoked biology at the level of both neural circuits and behavior in freely moving animals, critical to providing a mechanistic understanding of ultrasound neuromodulation.